Financial literacy externalities - Michael Chaliasos; Thomas Jansson; Yigitcan Karabulut (Sveriges Riksbank, 2016)
This paper uses unique administrative data and a quasi-field experiment of exogenous allocation of refugees in Sweden to estimate effects of exposure to financially literate neighbors on household financial behavior. The paper contributes evidence of a causal impact of financial literacy on behavior and points to a social multiplier of financial education initiatives. Exposure promotes saving for retirement in the medium run and stockholding in the longer run, more so when neighbors have economics or business education. Significant effects are only observed on educated or male-headed households. Findings point strongly to transfer of knowledge rather than mere imitation. They are relevant both for financial education and for refugee placement policies.
Keywords: G11; E21; D14; F22; I28; 330; Household finance; financial literacy; social interactions; refugees